TAX COMPLIANCE RISK AS AN ELEMENT OF THE TAX RISK MANAGEMENT CONCEPT IN AN ENTERPRISE - Olha Mashchenko; Anastasiia Khodus (Baltic Journal of Economic Studies)
Research subject. Compliance risk in the tax sphere, which is relevant today and provides for a constant increase in the level of voluntary compliance by taxpayers with the requirements of tax legislation by identifying and prioritising the risks of loss of tax revenues and implementing measures aimed at minimising tax risks. The study is based on changes in tax legislation, the introduction of a tax risk management system and indicators of tax efficiency of business entities at the legislative level. Methodology. Determination of the theoretical and methodological foundations of the tax compliance risk management system in the activities of enterprises together with innovations in the relevant legislative framework. Identification of the main risks, principles, segments of the tax compliance risk management system. Study of compliance risk indicators as one of the elements of improving the efficiency of tax risk management at the enterprise. The purpose of the study is to confirm the need to apply a tax compliance risk management system in the activities of business entities in the context of integration of domestic legislation and the modern economy in accordance with international standards. Determine the principles, segments and criteria of compliance risk introduced by the legislation. Determine the tax compliance risk indicators in accordance with the industry and class of business activity to ensure the appropriate level, which further ensures a reduction in the level of tax control over the entity's activities. Conclusion. The paper investigates the interpretation of compliance risk in the tax area as a set of measures for voluntary compliance with tax legislation. Implementation of a tax risk management system (compliance risk management) will ensure consistency and a unified approach to managing tax compliance risks for the State and business entities. The main compliance risks cover the processes from state registration of business entities to the final result - payment of taxes and fees to the budgets of all levels, which covers the process of administering taxes of business entities and is an integral part of business activities. The studied legislative principles of compliance risk based on international risk management standards provide for a comprehensive, flexible, focused and integrated tax risk management system, which at the same time is easy to adapt to the domestic economy. A new vector in the tax risk management system is the use of compliance risk indicators in the form of indicators of tax efficiency of business entities by industry and class of business, which will become the basis of a risk-oriented system in the future. Business entities, in turn, now have the opportunity to analyse these indicators to prevent and minimise tax compliance risks on their own using open data from tax authorities. The above-mentioned indicators and principles of compliance risk are an integral part of the tax risk management system (compliance risk) and their effectiveness depends on their comprehensive application in the activities of business entities and open co-operation with the tax authorities.